(untitled) (Research, Society and Development, 2020)
Objective: to report a health promotion intervention aimed at tracking systemic arterial hypertension, diabetes mellitus and raising awareness for adopting healthy eating habits. Methodology: a descriptive study, in the form of an experience report, which took place at a Federal Institute of Education, in November 2019, conducted by a multiprofessional health team with the institution’s outsourced professionals as its target audience. Results: the intervention took place in three interrelated moments: nursing consultation, consultation with a nutritionist and medical consultation. There was 40% adherence. Blood pressure, capillary blood glucose, body mass index and waist circumference were measured. As well as, guidelines on the adoption of healthy habits were offered, stimulating changes in lifestyle. Conclusion: health promotion strategies for the prevention of chronic diseases are relevant, as they encourage the adoption of healthy habits, avoiding complications and positively impacting quality of life. However, the culture of promoting health is incipient and the demand for assistance persists when illnesses become more acute. Therefore, it is necessary to strengthen and encourage interventions that can encourage individuals to become aware of the importance of adopting preventive measures. These are viable through health promotion actions.